STUDI ANALISIS EFEKTIVITAS JEMBATAN PENYEBERANGAN ORANG (JPO) STUDI KASUS : JPO JL. SISINGAMANGARAJA KOTA MEDAN - Johan Oberlyn Simanjuntak; Tiurma Elita Saragi; Nurvita Insani Simanjuntak; Andri Setiawan Mendrofa (Jurnal Darma Agung, 2021)
The pedestrian bridge (JPO), as part of the supporting facilities for the road transportation system, has an important role in the arrangement of the transportation system because in its planning the pedestrian bridge is planned to meet safety, security and comfort aspects and can be a liaison between areas that can be accessed by pedestrians. The research was conducted at the Sisingamangaraja Stree JPO which connects two (2) commercial areas, namely the Grand Mosque and the Yuki Simpang Raya shopping center which are generally crowded with residents of Medan City. Primary data collection in the field is carried out on the number of road crossings, both using JPO or not. The data finally shows that the Sisingamangaraja Street JPO is a JPO that is considered Effective as indicated by the percentage value of effectiveness is 61%. In addition, to show the correct crossing facilities on the road, traffic volume calculations are also carried out during peak hours which indicate that the correct crossing facility is a pelican with a waiting booth.